2018
DOI: 10.1002/bies.201800058
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Retroelement Expression and Nucleic‐Acid Immunity by Histone Methyltransferase SETDB1

Abstract: In human cancers, histone methyltransferase SETDB1 (SET domain, bifurcated 1) is frequently overexpressed but its significance in carcinogenesis remains elusive. A recent study shows that SETDB1 downregulation induces de-repression of retroelements and innate immunity in cancer cells. The possibility of SETDB1 functioning as a surveillant of retroelement expression is discussed in this study: the cytoplasmic presence of retroelement-derived nucleic acids (RdNAs) drives SETDB1 into the nucleus by the RNA-interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 92 publications
(139 reference statements)
0
18
0
Order By: Relevance
“…It hints at a correlation between the establishment of global H3K9 methylation and the suppression of retroelements. In reality, in somatic and embryonic stem cells, SETDB1/Trim28/KRAB-ZNF-mediated H3K9 methylation, separately from or in combination with DNA methylation, represses certain retroelement families ( 69 , 70 ). Additionally, LINE1 sequences are repressed in a target-specific fashion in the experiment using the TALE-L1-KRAB construct in mouse embryos ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…It hints at a correlation between the establishment of global H3K9 methylation and the suppression of retroelements. In reality, in somatic and embryonic stem cells, SETDB1/Trim28/KRAB-ZNF-mediated H3K9 methylation, separately from or in combination with DNA methylation, represses certain retroelement families ( 69 , 70 ). Additionally, LINE1 sequences are repressed in a target-specific fashion in the experiment using the TALE-L1-KRAB construct in mouse embryos ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to DNA methylation, histone methylation contributes to the repression of genomic retroelements. Retroelements are controlled by histone H3 lysine 9 methylation (H3K9me) catalyzed by SETDB1 [see (Kang, ) and references therein], G9A/GLP (Maksakova et al, ), and SUV39H1 and SUV39H2 (Bulut‐Karslioglu et al, ), and/or by H3 lysine 27 methylation (H3K27me) performed by the PRC2 complex involving EZH2 (Leeb et al, ). However, a recent study (Min, Park, Jeon, et al, ) has suggested that the expression levels of epi‐driver genes encoding these histone‐modifying enzymes and other related epigenetic modifiers were relatively stable and had little change during skeletal muscle aging.…”
Section: Discussionmentioning
confidence: 99%
“…Sedivy et al proposed an “aging‐by‐transposition” model, in which the retroelements and their transposases are the primary causes of structural dysregulation in the genome to manifest the aging phenotypes (Sedivy et al, ). It is notable that retroelement expression and transposition are also associated with cancer development (Kang, ; Lee et al, ) and neurodegenerative diseases (Reilly, Faulkner, Dubnau, Ponomarev, & Gage, ; Tan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation may be that HERV elements (and, by extension, HERV-derived REs) are subject to strong epigenetic controls that keep them essentially silent, except in cancer, autoimmunity and placental development (Hurst & Magiorkinis, 2017). Another explanation may be based on a recent report (Kang, 2018) suggesting that tumour-initiating cells must have repressed HERV elements, since their expression produces different types of RNAs that elicit interferon response and apoptosis, leading to cancer cell death. On the other hand, HERV silencing enables cancer protection against lethal drug exposure, promotes immune evasion, and progresses to fully established cancer.…”
Section: Discussionmentioning
confidence: 99%